Baking - Peterson, Wendy Jo (--For dummies., 2023)
"Baking For Dummies is your go-to source for basic instructions and easy-to-follow recipes. Learn to make delicious and impressive cookies, cakes, breads, cupcakes, frostings, pies, muffins, cobblers, quiches, and beyond. Elevate your next get together by crafting a dessert charcuterie board or serving decadent individual quiches, savory scones, and homemade rolls-it's a step up from store bought cookies and cakes, for sure. In this low-key Dummies guide, you'll find lists of basic ingredients and essential equipment, plus explanations of baking techniques and definitions of baking terms and techniques you'll need to know. This book also covers basic kitchen prep, time-saving tricks, kid-friendly baking recipes, allergy and dietary modifications-this book has it all"--